System of Measuring PH, Humidity, and Temperature Based on Internet of Things (IoT) - Eka Sari, Wahyuni; Junirianto, Eko; Fatur Perdana, Geofani (Buletin Ilmiah Sarjana Teknik Elektro, 2021)
The problem faced by farmers in Samarinda is the difficulties to know the condition of the chili plants when they are away from home or from the garden. Often times the farmer commutes from home to the garden just to monitor the condition of the plants, which reduces work effectiveness and takes a long time. Therefore, in this study a tool was made to measure soil moisture, temperature and soil pH based on the Internet of Things. The process of monitoring soil pH, soil moisture, and air temperature in chili plants using soil pH sensors, soil moisture sensors, and soil temperature sensors as well as Wemos / Arduino for data processing and sending analog data to the ANTARES platform. The result of this research is that soil condition data can be sent and read in real time through the ANTARES web application. Tool testing was carried out at 30 different locations in the city of Samarinda.